Organic pollutant oxidation on manganese oxides in soils – the role of calcite indicated by geoelectrical and chemical analyses - S. S. Altzitser; Y. G. Mishael; N. Schwartz (SOIL)
Understanding phenolic-pollutant interactions with soil colloids has been a focus of extensive research, primarily under controlled conditions. This study addresses the need to explore these processes in a more natural, complex soil environment. We aim to shed light on the underlying mechanisms of hydroquinone (a representative phenolic pollutant) oxidation in ambient, MnO2-rich sandy soil within soil columns designed for breakthrough experiments. Our innovative approach combines noninvasive electrical measurements, crystallographic and microscopic analyses, and chemical profiling to comprehensively understand soil–pollutant interactions. Our study reveals that hydroquinone oxidation by MnO2 initiates a cascade of reactions, altering local pH, dissolving calcite, and precipitating amorphous Mn oxides, thereby showcasing a complex interplay of chemical processes. Our analysis, combining insights from chemistry and electrical measurements, reveals that the oxidation process led to a constant decrease in polarizing surfaces, as indicated by quadrature conductivity monitoring. Furthermore, dynamic shifts in the soil solution chemistry (changes in the calcium and manganese concentrations, pH, and electrical conductivity (EC)) correlated with the non-monotonous behavior of the in-phase conductivity. Our findings conclusively demonstrate that the noninvasive electrical method allows real-time monitoring of calcite dissolution, serving as a direct cursor to the oxidation process of hydroquinone and enabling the observation of chemical interactions in soil solution and on soil particle surfaces.